2018
DOI: 10.1253/circj.cj-17-0986
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Score Efficiently Prevents Tolvaptan-Induced Hypernatremic Events in Patients With Heart Failure

Abstract: tions were reported to occur following tolvaptan treatment in a dose-dependent manner, with rates of 6%, 11%, and 13% for 30, 45, and 60 mg tolvaptan, respectively. 7 Although the risk of hypernatremia was not clear in the pivotal Phase 3 QUEST study, 8 we reported 3 risk factors for hypernatremic events using the interim results of the Samsca Post-Marketing Surveillance In the Heart faiLurE (SMILE) study conducted in 2014. 9 These factors were higher baseline sodium concentration, lower baseline potassium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 12 publications
2
31
4
Order By: Relevance
“…An interim analysis of the SMILE study in 1,053 evaluable patients reported significant improvement or absence of lower limb edema, pulmonary congestion, dyspnea, jugular venous distention, and hepatomegaly at Days 7 and 14 (P<0.0001 for all symptoms). 16 This final analysis confirms the interim results and indicates clinically meaningful symptom-free rates also for 3rd sound and rales.…”
Section: Baseline Characteristics According To Outcomesupporting
confidence: 75%
See 1 more Smart Citation
“…An interim analysis of the SMILE study in 1,053 evaluable patients reported significant improvement or absence of lower limb edema, pulmonary congestion, dyspnea, jugular venous distention, and hepatomegaly at Days 7 and 14 (P<0.0001 for all symptoms). 16 This final analysis confirms the interim results and indicates clinically meaningful symptom-free rates also for 3rd sound and rales.…”
Section: Baseline Characteristics According To Outcomesupporting
confidence: 75%
“…Risk factors for tolvaptan-induced hypernatremic events have previously been analyzed and reported in detail. 16 A risk score nomogram based on the final SMILE dataset has been developed to identify at-risk patients who should begin tolvaptan treatment at a dosage of 3.75 mg/day. Although cases of elevated liver enzymes related to tolvaptan were reported in clinical trials of patients with autosomal dominant polycystic kidney disease, 17 the tolvaptan dosage was much higher (60-120 mg/ day) than that indicated for use in patients with HF.…”
Section: Study Limitationsmentioning
confidence: 99%
“…We recently proposed a scoring system to predict the occurrence of hypernatremic events, and age is a strong risk factor for hypernatremia, particularly when tolvaptan was administered at a high dose (i.e. 15 mg/day) [24]. A low starting dose (i.e.…”
Section: Elderly Populationsmentioning
confidence: 99%
“…Sometimes, hypernatremia results in central nervous system disturbance. There is a population that is a risk to the development of hypernatremia [14], and risk factors for hypernatremia in tolvaptan treatment were previously reported [9][10][11]. This study aimed to elucidate clinical factors associated with hypernatremia in patients with ADHF treated with full medications and tolvaptan in real-world practice.…”
Section: Backgroundsmentioning
confidence: 99%
“…The serum sodium level increases as a result of aquaresis in almost all cases, and hypernatremia can be lethal in some patients [7,8] and was identi ed as a signi cant adverse event to be prevented [9]. Therefore, a lower dose of tolvaptan to prevent hypernatremia has been recommended in the initial phase [10,11], because tolvaptan treatment can dose dependently lead to abnormal hypernatremia [12,13]. Sometimes, hypernatremia results in central nervous system disturbance.…”
Section: Backgroundsmentioning
confidence: 99%